Electromechanical properties of flexible piezoelectric nanogenerator (PENG) using different patterns of vertically-aligned BaTiO3 nanotubes - Aleman, Camelle Kaye A.; Narvaez, James Albert B.
With the advancement catered by the use of lead-free piezoelectric nanogenerators (PENG) for flexible electronics, the challenge is to design an efficient system with high power output. In this light, the patterning effects of a piezoelectric material, barium titanate (BaTiO3) nanotubes, on the electromechanical properties of a PENG device is explored in this study. Four different patterns of vertically-arrayed, tetragonal phase BaTiO3 nanotubes were synthesized via in situ conversion of selectively-anodized TiO2 nanotubes using hydrothermal process. Using this material, a piezoelectric nanogenerator (PENG) device was constructed to transform mechanical energy into usable electrical energy. The PENGs comprised a sandwich structure of Ti- BaTiO3-graphite-Ti and were further made flexible by encapsulating the structure with polydimethylsiloxane. The cantilever-type PENG devices were subjected to repeated bending stresses using a rotating motor to determine the effect of different BaTiO3 patterns on the devices' output voltages under constant cyclical stress. The highest output voltage generated reached up to 1.9 V. Moreover, the study showed that decreasing the BaTiO3 nanotube array spacing and the diameter of the pattern, increases the lateral displacement of the piezoelectric material; therefore, increasing the output voltage of the device.